PENGARUH PERSEPSI HARAPAN ORANG TUA DAN SELF-EFFICACY TERHADAP FEAR OF FAILURE PADA PEREMPUAN SULUNG DEWASA AWAL DIKABUPATEN KARAWANG: Psikologi - Rifqa Azita; Wina Lova Riza; Mohamad Sopian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Previous studies on fear of failure have generally focused on students or adolescents, while research specifically examining firstborn women in early adulthood, particularly within the social context of Karawang Regency, remains limited. This study examined the predictive roles of perceived parental expectations and self-efficacy in fear of failure among firstborn women in early adulthood in Karawang Regency. A quantitative approach with a predictive correlational design was employed. The participants comprised 349 firstborn women aged 18–40 years who lived in Karawang Regency and were recruited using snowball sampling. Data were collected using the Perception of Parental Expectations Inventory (POPEI), the General Self-Efficacy Scale (GSE), and the Performance Failure Appraisal Inventory (PFAI), and were analyzed using multiple linear regression. The findings showed that perceived parental expectations and self-efficacy jointly and significantly predicted fear of failure. Perceived parental expectations were a positive predictor, whereas self-efficacy was a negative predictor of fear of failure. Higher perceived parental expectations were associated with a greater tendency to experience fear of failure, whereas higher self-efficacy was associated with a lower tendency to experience it. These findings highlight the importance of realistic, open, and supportive parental communication, as well as efforts to strengthen self-efficacy, to support the psychological well-being of firstborn women in early adulthood. ABSTRAK Penelitian mengenai fear of failure umumnya berfokus pada mahasiswa atau remaja, sedangkan kajian yang secara khusus menelaah perempuan sulung dewasa awal, terutama dalam konteks sosial Kabupaten Karawang, masih terbatas. Penelitian ini bertujuan menganalisis peran prediktif persepsi harapan orang tua dan self-efficacy terhadap fear of failure pada perempuan sulung dewasa awal di Kabupaten Karawang. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional prediktif. Partisipan penelitian berjumlah 349 perempuan sulung berusia 18–40 tahun yang berdomisili di Kabupaten Karawang dan direkrut menggunakan teknik snowball sampling. Data dikumpulkan menggunakan Perception of Parental Expectations Inventory (POPEI), General Self-Efficacy Scale (GSE), dan Performance Failure Appraisal Inventory (PFAI), kemudian dianalisis menggunakan regresi linear berganda. Hasil penelitian menunjukkan bahwa persepsi harapan orang tua dan self-efficacy secara simultan memprediksi fear of failure secara signifikan. Persepsi harapan orang tua menjadi prediktor positif, sedangkan self-efficacy menjadi prediktor negatif terhadap fear of failure. Semakin tinggi harapan orang tua yang dipersepsikan, semakin tinggi kecenderungan perempuan sulung mengalami fear of failure. Sebaliknya, semakin tinggi self-efficacy, semakin rendah kecenderungan tersebut. Temuan ini menegaskan pentingnya komunikasi harapan orang tua yang realistis, terbuka, dan suportif serta penguatan self-efficacy untuk mendukung kesejahteraan psikologis perempuan sulung dewasa awal.